The Influence of Audit Committees, Independent Commissioners, Company Size and Audit Quality on Report Integrity - Permata Kusumaningrum; Abdul Rohman (Eduvest - Journal of Universal Studies, 2025)
This study aims to obtain empirical evidence regarding the influence of the audit committee on financial statement integrity, the influence of independent commissioners on financial statement integrity, the influence of company size on financial statement integrity, and the influence of audit quality on financial statement integrity. The sample in this study consists of property and real estate companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The total sample in this study is 45 data points. Data collection was conducted through the official IDX website and the official websites of property and real estate companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The data analysis technique used in this study is multiple linear regression analysis with SPSS 18.0 software. The results of data processing tests show that the audit committee has a positive effect on financial statement integrity, while the influence of independent commissioners, company size, and audit quality negatively affects financial statement integrity.